Pengaruh Kejelasan Sasaran Anggaran, Budaya Organisasi, Pengendalian Akuntansi, Sistem Pelaporan, Dan Motivasi Kerja Terhadap Akuntabilitas Kinerja Instansi Pemerintah (Studi Empiris pada Satuan Kerja Perangkat Daerah Dinas di Kota Surakarta) - Khasanah, Dewi Nur, Enny Kusumawati,SE.,MM.,AK,CA (2016)
Performance accountability have come to one of item contained in legal fundament organizational order or organization obliged judicially to fulfill it was organization accountability with the performance which was obtained. This research was purpose to analyse the influence of clarity of budget target, organization cultural, accounting control, reporting system, and job motivation to governmental accountability institution performance at SKPD in Surakarta City. This research was using quantitative, by the data source in the form of primary data obtained from questioner. Sum up the sample research counted 63 responders taken by purposive sampling. Analyzer used cover data quality test, classic assumption test, multiple linear regressions analyze and hypothesis test covering F test, coefficient determinasi R2 test, and t test. The results of analysis can be conclusion that clarity of budget target, organization cultural, accounting control, reporting system, and job motivation has an influence to governmental accountability institution performance at SKPD in Surakarta City, this matter was shown by p value was each variable < 0,05. So that hypothesis from H1 until H5 was truth acceptable.